Pengaruh Pemberian Tepung Biji Nangka (Artocarpus heterophyllus) Dalam Pakan Terhadap Berat Organ Dalam Ayam Pedaging - Satria; Marhayani; Serli; Syadik, Fajar (Universitas Madako Tolitoli, 2026)
This study aims to determine the effect and best level of providing jackfruit seed flour in feed on organic weight in broiler chickens. This study was conducted from November to December 2024 in a pen owned by SMK Negeri 1 Galangi, Tolitoli Regency. This study used 80 2-week-old broiler chickens from CV. Primadona. This study used a Completely Randomized Design (CRD) with 4 treatments and 4 replications, resulting in 16 cages with 5 chickens in each unit. The treatments in this study consisted of P0 = 100% basal feed without the addition of jackfruit seed flour (Artocarpus heterophylus), P1 = Basal feed + jackfruit seed flour (Artocarpus heterophylus) 2%, P2 = Basal feed + jackfruit seed flour (Artocarpus heterophylus) 4%, P3 = Basal feed + jackfruit seed flour (Artocarpus heterophylus) 6%. The results of this study showed that the provision of jackfruit seed flour (Artocarpus heterophylus) in broiler chicken feed did not significantly affect the weight of internal organs of broiler chickens during 3 weeks of maintenance. The average value of the heart organ weight was P0 (0.47), P1 (0.52), P2 (0.45) and P3 (0.57). The average values for liver organ weights were P0 (2.92), P1 (2.84), P2 (3.02), and P3 (2.80). Meanwhile, the average values for gizzard organ weights were P0 (1.67), P1 (1.68), P2 (1.81), and P3 (1.70). The organ weights of broiler chickens measured in this study were within the normal range